Studi Tingkat Bahaya Gerakan Massa Tanah/Batuan Di Kota Manado Bagian Selatan, Sulawesi Utara = Study on SoiVRock Mass Movement Hazard Rate of Southern. Manado, North Sulawesi, Indonesia - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
ABSTRACT The objectives of this research are : (1) to study factors influencing the types and the number of mass movement occurrence, (2) to investigate the rate and to evaluate the spatial distribution of soil/rock mass movement hazard. A survey method with a purposive sampling technique was used. A terrain unit was adopted for the mapping units arranged on the bases of landforms, slopes and land-uses. An evaluation on the rate of mass movement hazard was conducted by adding up the values of terrain characteristics and mass movement occurrence variables due to mass movement and population density. A variance analysis was carried out to find out whether the variable of the terrain characteristics exerts some different influence on the rate of mass movement. The rate of mass movement hazard of the terrain unit were classified into five categories, namely non, low, medium, high, and very high hazard. The results of study showed that there were 4 types of mass movement over the study area, namely creeping, landslide, slump, soil/rock fall total with 303 occurrences. The distribution of types and the number of the mass movement occurrence were influenced by terrain characteristics. The eroded denudational hilly landform (D2) experienced the mass movement at the greatest extent. The levels of soil/rock mass movement hazard over the study areas varied from non-hazard to high hazard categories. Non-hazard, low hazard, medium hazard, and high hazard rate were found in 7, 11, 1, and 2 terrain units respectively. Medium hazard rate found in terrain unit (D2 III Pr) covered 10 village areas of 3.12 km2. the area influenced by mass movement 0.67 km2, experiencing 39 mass movement occurrences. The high hazard rate of mass movement was found in the terrain unit (D2 IV Pr and D2 V Pr) included 14 village areas of 5,58 km2. The area influenced by the mass movement was 1,78 km2, experiencing 197 mass movement occurrences.